2012
DOI: 10.1097/ico.0b013e318269c9cd
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Vision in Eyes After Selective Lamellar Keratoplasty

Abstract: With the increasing popularity of selective lamellar keratoplasty procedures, it is important to characterize the optical differences among penetrating keratoplasty (PK), deep anterior lamellar keratoplasty (DALK), and Descemet stripping automated endothelial keratoplasty (DSAEK). The impact of optical differences on the visual acuity (VA) in eyes after keratoplasty is significant. Quantitative evaluation of corneal higher-order aberrations (HOAs) of anterior and posterior surfaces using a rotating Scheimpflug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
3
32
0
1
Order By: Relevance
“…68 42% DSAEK eyes exhibited an anterior peak pattern, with a single sharp peak in the anterior cornea. 68 Visual acuity correlated significantly with corneal scatter, and the results suggested that increased light scatter originated from both the anterior and posterior cornea after DSAEK. 68 The effects of light scatter on visual acuity and contrast sensitivity may be more apparent in everyday life, with varying ambient lighting and sources of glare in the environment.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 76%
See 3 more Smart Citations
“…68 42% DSAEK eyes exhibited an anterior peak pattern, with a single sharp peak in the anterior cornea. 68 Visual acuity correlated significantly with corneal scatter, and the results suggested that increased light scatter originated from both the anterior and posterior cornea after DSAEK. 68 The effects of light scatter on visual acuity and contrast sensitivity may be more apparent in everyday life, with varying ambient lighting and sources of glare in the environment.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 76%
“…54,138 Although correlation has been demonstrated between anterior corneal HOAs and postoperative BCVA, 84,108,137,139 several studies have failed to find a similar association between posterior corneal HOAs and postoperative BCVA. 68,81,84,133,137 Despite this, the impact of the posterior corneal surface on visual outcomes should not be ignored. …”
Section: Influence Of the Posterior Cornea (Donor Graft)mentioning
confidence: 99%
See 2 more Smart Citations
“…Fatores relacionados à superfície ocular e ao segmento anterior incluindo a dinâmica do filme lacrimal, aberrações corneanas de baixa e alta ordem, opacidades anteriores ou posteriores e descentrações pupilares podem ser responsáveis por resultado visual insatisfatório. 40 Dirisamer et al…”
Section: Discussionunclassified